× Didn't find what you were looking for? Ask a question
  
  
Top Posters
Since Sunday
j
6
l
6
p
5
n
5
N
5
m
5
j
4
s
4
g
4
c
4
r
4
m
4
New Topic  
nini07 nini07
wrote...
Donated
Posts: 385
8 years ago
note that x2 means x squared.

find the type & number of solutions for each equation
59.x2-6x= -5
61, x2-245x=-144
63. 3x2-5x+3=0
Read 2386 times
7 Replies
HOPE*FAITH*LOVE

Related Topics

Replies
wrote...
Donated
Valued Member
8 years ago
\({{x}^{2}}-6{x}=-5\)

Something like this?

As you can tell, it's a quadratic!

\({{x}^{2}}-6{x}+5=0\)

Now you solve for x:

\({{x}^{2}}-6{x}+5=0\)

Or, you can factor out an \({x}\):

\({x}({x}-6)=5
{x}=-5
{x}-6=-5
{x}=-5+6
{x}=1
\)

So our \({x}\) values are: -5 and 1

I will work on the rest for you.

I love this math module! Genius Idea Face with Rolling Eyes
wrote...
Donated
Valued Member
8 years ago
Woops I made a mistake with the factoring in the previous question Undecided
wrote...
Educator
8 years ago
Yeah, I can see you're struggling, why don't you put it in vertex form and from there, solve for the x's?
The best way to say thank you is with a positive review:

  Click here to review us!
wrote...
Educator
8 years ago
Lets start with where you left off from, Star.

\(x2 - 6x = -5\)

x2 - 6x + 5 = 0

You need to find factors of \(5\) that add up to \(6\)... Let's try \(5 * 1 = 5\), but when we add them, we get \(+6\). So that won't work.

Since, it's not working, we have to convert it into vertex form by completing the square and then manually solving for \(x\).

\(x2 - 6x + 5 = 0\)

\(\frac{-6}{2}=(-3)^2=9

x2 - 6x + 9 - 9 + 5 = 0
(x-3)^2 - 4=0
\)

Now solve for \(x\):

\({sqrt{\4}} = {sqrt{\(x-3)^2}}\)

+/-\(2 = x-3\)

if +2: 2 + 3 = \(x = 5\)
if -2: -2 + 3 = \(x = 1\)

Don't forget to write a "therefore" statement Slight Smile
The best way to say thank you is with a positive review:

  Click here to review us!
wrote...
Donated
Valued Member
8 years ago
Awesome, but we ended up getting the same answers Smiling Face with Open Mouth and Tightly-closed Eyes, so I guess I was going it right afterall. Nini, are you ok with the other two or would u like me to answer them as well? Smiling Face with Open Mouth
wrote...
Educator
8 years ago
61. \(x^2-245x+144 = 0\)

\(x^2-245x +\)\(({\frac{245}{2})^{2}}\)\(-({\frac{245}{2})^{2}}\)\( +144 = 0\)

\((x - \frac{245}{2})^2 - 14862.25 = 0

+{sqrt{\14862.25}} + \frac{245}{2}= x = 244.41
-{sqrt{\14862.25}} + \frac{245}{2}= x = 0.58917
\)

The best way to say thank you is with a positive review:

  Click here to review us!
wrote...
Donated
8 years ago
SO FAR IM DOING GOOD WITH THE OTHERS I JUST NEED HELP WITH THE MORE ALGEBRA PART.   THANK YOU
HOPE*FAITH*LOVE
New Topic      
This topic is not open for further replies. If you'd like to contribute to this topic, start a new thread and make reference to this one. Otherwise, contact a moderator for more options.
Explore
Post your homework questions and get free online help from our incredible volunteers.
Learn More
Improve Grades
Help Others
Save Time
Accessible 24/7
  48 People Browsing
 202 Signed Up Today
Your Opinion
What's your favorite coffee beverage?
Votes: 70

Related Images
 3269
 75
 34